Potential Carbon Stock and Absorption in Mangroves in Penempul Village, Sungai Sembilan District, Dumai City, Riau Province - Yuhanda, Sabina Dwi; Siregar, Yusni Ikhwan; Tanjung, Afrizal (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Global warming is caused by increased greenhouse gas emissions, particularly CO₂, and can be controlled through carbon sequestration by vegetation, including mangrove forests. The study was conducted in January and February 2025 in the mangrove area of Penempul Village, Sungai Sembilan District, Dumai City, Riau Province, to determine the density in relation to biomass, carbon stock, and CO₂ absorption, as well as to investigate the relationship between density and biomass, carbon stock, and CO₂ absorption. The method used in this study was a survey method with a purposive sampling technique, which involved measuring the diameter of mangrove tree trunks at chest height (DBH). Mangrove biomass calculations were performed using allometric equations, and biomass was converted into carbon stock and CO₂ absorption. The study results indicated the presence of 11 mangrove species, with average estimated biomass, carbon stock, and CO₂ absorption values of 521.84 tons/ha, 245.25 tons/ha, and 899.35 tons/ha, respectively. The ANOVA results showed significant differences (p > 0.05) between the three stations regarding biomass, carbon stock, and CO₂ absorption. Mangrove density had a weak correlation with biomass, carbon stock, and CO₂ absorption, with a correlation coefficient of 0.299.